2-14=12y+9-11y

Simple and best practice solution for 2-14=12y+9-11y equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2-14=12y+9-11y equation:


Simplifying
2 + -14 = 12y + 9 + -11y

Combine like terms: 2 + -14 = -12
-12 = 12y + 9 + -11y

Reorder the terms:
-12 = 9 + 12y + -11y

Combine like terms: 12y + -11y = 1y
-12 = 9 + 1y

Solving
-12 = 9 + 1y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-1y' to each side of the equation.
-12 + -1y = 9 + 1y + -1y

Combine like terms: 1y + -1y = 0
-12 + -1y = 9 + 0
-12 + -1y = 9

Add '12' to each side of the equation.
-12 + 12 + -1y = 9 + 12

Combine like terms: -12 + 12 = 0
0 + -1y = 9 + 12
-1y = 9 + 12

Combine like terms: 9 + 12 = 21
-1y = 21

Divide each side by '-1'.
y = -21

Simplifying
y = -21

See similar equations:

| 7p+6+2p= | | -5/6n+8=-32 | | .25+x=-.583 | | .5m-7=-4 | | x^4+3x^3-4x^2-12=0 | | -5u+15=7(u-3) | | 2x-18=5(x+3) | | t-(-4)=18 | | x+35/5=8 | | 30w^2+19w+2= | | 16x^2+16x+3= | | 18m^2-15m+2= | | -2(7k-3)=-92 | | (x^2+3x-44)/(x+7) | | 4y^2-17y+15= | | 3x-12-9=2x-6 | | g-340=95 | | 5x^2-46x=0 | | 2d/3=-14 | | 4n-26=5 | | 12w^2-4w-5= | | (7z/3)-2=3z-9 | | 4x-3x+9=0 | | (h+h)+2=250 | | Y+(y/3)=12 | | 16x^3-6x=4x^2 | | 3x-3=2y-4 | | P^2-p-42= | | 4+(5(7-x)/9)=-1 | | -2y=2x-1 | | 11x+y=21 | | 4x-8=x+13 |

Equations solver categories